Electronic communications regulation in Europe: An overview of past and future problems - Pier Luigi Parcu; Virginia Silvestri (International Telecommunications Society (ITS), 2013)
For many years electronic communications has been one of the most important areas of policy intervention for the European Union. Liberalisation and privatisation of the telecommunications industry have been very important topics of the policy debate in the two decades starting from 1990 to 2010. In these years the EU developed a sophisticated regulatory framework inspired to the principle of favouring entrance of new players in the sector and characterised by a strong pro-competition flavour. More recently, however, the necessity to mobilise important investments for the creation of new Next Generation Networks, capable of delivering to European citizens all the benefits of the digital revolution, has shed doubts on the validity of the established framework. This paper discusses the solutions adopted during the liberalisation process and summarizes some of the key future challenges to the existing regulatory framework.
Keywords: K23; L43; L51; L96; 330